2021
DOI: 10.1080/14767058.2021.1956895
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of symptoms affect pregnancy outcomes in third trimester in women with SARS-CoV-2

Abstract: Objective: Parturients with symptoms to COVID-19 have an increased risk for neonatal adverse outcomes and for any adverse outcome compared to the asymptomatic COVID-19 positive parturients and to the COVID-19-negative parturients. The purpose of this study was to determine the effect of COVID-19 on obstetric outcomes based on symptom status of parturients at or near term. Methods: Retrospective cohort study of parturients diagnosed with COVID-19 between 26 March and 30 September 2020. Maternal and neonatal out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In Israel, scarce studies exist on the prognosis of COVID-19 in pregnant women. Two studies have shown that the most common symptom observed in this population is cough ( Harel et al, 2021 ) and that the disease presents mostly as a mild or an asymptomatic one ( Rottenstreich et al, 2021 ). The majority of pregnant women were in their third trimester at the time of COVID-19 diagnosis and delivery ( Mohr-Sasson et al, 2020 ; Barber et al, 2021 ; Harel et al, 2021 ; Rottenstreich et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Israel, scarce studies exist on the prognosis of COVID-19 in pregnant women. Two studies have shown that the most common symptom observed in this population is cough ( Harel et al, 2021 ) and that the disease presents mostly as a mild or an asymptomatic one ( Rottenstreich et al, 2021 ). The majority of pregnant women were in their third trimester at the time of COVID-19 diagnosis and delivery ( Mohr-Sasson et al, 2020 ; Barber et al, 2021 ; Harel et al, 2021 ; Rottenstreich et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…Two studies have shown that the most common symptom observed in this population is cough ( Harel et al, 2021 ) and that the disease presents mostly as a mild or an asymptomatic one ( Rottenstreich et al, 2021 ). The majority of pregnant women were in their third trimester at the time of COVID-19 diagnosis and delivery ( Mohr-Sasson et al, 2020 ; Barber et al, 2021 ; Harel et al, 2021 ; Rottenstreich et al, 2021 ). Vaginal delivery was the most common, followed by C-section that was mainly performed based on obstetric indication and not due to the SARS-CoV-2 infection ( Mohr-Sasson et al, 2020 ; Barber et al, 2021 ; Rottenstreich et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 1 more Smart Citation